PROTECTION OF CHILDREN'S RIGHTS IN CUSTODY DISPUTES AWARDING GUARDIANSHIP TO GRANDPARENTS FROM THE PERSPECTIVE OF THE CONVENTION ON THE RIGHTS OF THE CHILD - Anggraini, Ratu Mutiara; Tjempaka, Tjempaka (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The protection of children’s rights constitutes a fundamental legal and social concern because it directly affects children’s future, welfare, and development as vulnerable legal subjects; in custody disputes, the judiciary plays a pivotal role in ensuring that the best interests of the child remain the paramount consideration. Although the international framework, notably the Convention on the Rights of the Child, and national regulations affirm this principle, judicial practice reveals implementation complexities shaped by social, psychological, and economic factors. This study aims to analyze the application of the best interest of the child principle in custody dispute rulings (case study: Decision No. 167/Pdt.G/2021/PN Plk) and its implications for child protection. The research employs a normative-empirical juridical method through statutory and doctrinal review combined with case law analysis as empirical evidence. The findings indicate that judges tend to prioritize the child’s holistic welfare by weighing factual evidence concerning caregivers’ financial capacity, emotional stability, and any conduct endangering the child; in the examined case, custody was transferred to the grandparents due to substantiated concerns about the biological parent’s fitness. Moreover, the study reveals procedural shortcomings such as the sporadic use of systematic child-psychological expert testimony and weak post-decision monitoring mechanisms that leave residual risks to children’s rights. The research further highlights the need to harmonize international norms with domestic practice, to incorporate standardized psychosocial assessment tools into adjudicative processes, and to establish regular oversight of enforcement. Consequently, judicial decisions grounded in the best-interest principle must be supported by multidisciplinary procedures and enforceable follow-up measures to ensure effective protection of children’s rights.